AGENDA SETTING, NAWACITA, DAN PIDATO KENEGARAAN: ANALISIS ISI PIDATO KENEGARAAN PRESIDEN RI TAHUN 2014-2019 - listya nanda, dea; Maserona Sarungu, Lukas (JURNAL KOMUNITAS, 2026)
This study was motivated by the need to evaluate how far President Joko Widodo’s state addresses reflect the nine priority agendas of Nawacita during the 2014–2019 administration. The main issue lied in the absence of quantitative research specifically measuring the representation of Nawacita agendas in official state communication. The objective of this research was to identify the frequency of Nawacita themes in the President’s speeches and determine which agendas are most prioritized. This study applied Agenda Setting Theory (McCombs & Shaw) using a quantitative content analysis method on six state speech texts (2014–2019). The unit of analysis consisted of words/phrases categorized into nine Nawacita points. The findings reveal that Nawacita 1 (national protection), Nawacita 5 (human development), and Nawacita 7 (economic independence) appear most frequently, highlighting the administration’s focus on national security, human capital, and domestic economy. This research contributes to filling the literature gap, which has mostly employed qualitative approaches, and affirms that state addresses are not merely symbolic rhetoric but also reflections of concrete government policies.